Sex Differences in Age of Diagnosis and First Concern among Children with Autism Spectrum Disorder. Issue 5 (3rd September 2021) - McDonnell, Christina G.; DeLucia, Elizabeth A.; Hayden, Elizabeth P.; Penner, Melanie; Curcin, Kristina; Anagnostou, Evdokia; Nicolson, Rob; Kelley, Elizabeth; Georgiades, Stelios; Liu, Xudong; Stevenson, Ryan A.
ABSTRACT: Objective: Early identification of autism spectrum disorder (ASD) is an essential healthcare priority. Girls may be at risk for late diagnosis, although research is equivocal regarding how sex and other factors relate to ASD identification. The goals of the current investigation were to (1) identify how child sex, cognitive abilities, and demographic factors relate to age of first concern (AOC) and age of diagnosis (AOD), (2) evaluate trends in AOC/AOD over time, and (3) consider whether main effects of sex on AOC/AOD are moderated by cognitive abilities or time. Method: Children (N = 365; 20% female; 85.6% identified as White) with ASD participated through the Province of Ontario Neurodevelopmental Disorders (POND) Network. Study records included AOD, date/timing of diagnosis (between 1996 and 2017), age of first parent concern, demographics, and standardized cognitive testing results (24.7% of children had IQ scores below standard scores of 70). Results: Average AOC occurred before 2 years of age whereas average AOD occurred after 5 years of age. Girls did not differ on AOC but had a later AOD than boys. Higher verbal IQ was associated with later AOD more strongly in girls than boys. Regarding time-related changes, average AOC and AOD increased across the study period, more strongly for girls. Conclusions: Results support that sex is a key factor underlying delays in ASD identification and highlight the urgent need to improve diagnostic practices among girls. Limitations and implications for improving the diagnostic process are discussed. Abbreviations: ASD=autism spectrum disorder; IQ=intelligence quotient; AOC=parental report of age of first concern; AOD=age of diagnosis.